Phase separation in epigenetics and cancer stem cells - Xiao, Chanchan; Wu, Guangjie; Chen, Pengfei; Gao, Lijuan; Chen, Guobing; Zhang, Hongyi (Frontiers in Oncology, 2022)
Accumulating evidence indicates that liquid–liquid phase separation (LLPS) is the basis of the formation of membrane-less compartments in cells. This biomolecular condensate represented by phase separation may influence epigenetics in cancer stem cells (CSCs), a small subpopulation of cancer cells responding to the initiation, maintenance, metastasis, and therapy resistance of cancer. Understanding the underlying biophysical principles and the specific characteristics of biocondensates would provide insights into the precise blocking of potential tumor targets, thereby fundamentally curbing tumor occurrence, recurrence and metastasis. In this review, we summarized the key phenomenon and experimental detection of phase separation and the possibility of regulating the stemness of CSCs through phase separation. We believe that the mechanism of phase separation in CSCs will open up new avenues for the mystery of tumor formation, and modulating phase separation will be a great strategy for CSC-targeted tumor therapy.